Diversity and Inclusion Practices in Nonprofit Associations: A Resource-Dependent and Institutional Analysis - Dyana P. Mason (Journal of Public and Nonprofit Affairs, 2020)
Since the early 1990s, diversity and inclusion (D&I) efforts have received increasing attention among management scholars. Although the benefits and challenges of implementing D&I practices are now well established, few studies have explored the extent to which nonprofit associations, in particular, engage in D&I efforts. As such, we have no knowledge of the role that associations play in assisting with the diffusion of these practices throughout their respective professional fields or trades. Therefore, using a national survey of over 150 executives of nonprofit associations, this study explores the institutional and resource-based challenges associations face when seeking to implement D&I practices, both within their organizations and throughout their professional fields and trades. While the findings from this study suggest that nonprofit associations only engage in D&I practices to a modest degree, there is also evidence of institutional entrepreneurship. Implications of these findings for research on D&I practices in nonprofit associations as well as for association practitioners seeking to improve their D&I programming are provided.